Pengaruh Motivasi Kerja, Fleksibilitas Jam Kerja, Dan Stres Kerja Terhadap Kinerja Karyawan Pada Warkop DKI Lagi Kota Malang - Wardani, Putri Kusuma; Djaelani, Abdul Kodir; Novianto, Abdullah Syakur (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This study aims to identify the effect of motivation, flexibility, and stress on employee performance at Warkop DKI Lagi Malang City. This study uses quantitative methods. The population of this research employees Warkop DKI Lagi Kota Malang by using a saturated sample, as many as 45 respondents. Methods of data collection using a questionnaire. The analytical method used in this study is multiple regression analysis with SPSS 26 for windows. The results of this study indicate a significant positive influence among the variables of motivation, flexibility, and stress on employee performance at Warkop DKI Lagi in Malang City. Keywords: Motivation, Flexibility, and Stress